The functions of gibberellin in different tissues of the tomato plant (Solanum lycopersicum L.) - Martins, Auxiliadora Oliveira (2017)
This thesis is largely focused on improving the current understanding about the role played by gibberellins (GAs) levels in different tissues and in the fruit development process. Two well- defined goals were established: (I) to gain more insights into how and to which extent manipulation of GA levels might differently affect plant growth in general; (II) to generate experimental evidences for the role GAs play during the transition from vegetative to reproductive phase. For this, we firstly reviewed the current evidence of the connection between central energy and GAs metabolism, via the tricarboxylic acid (TCA) cycle. The key point at this process is the 2- oxoglutarate, a TCA cycle intermediate, which has been suggested to play a role in the control of GA biosynthesis. This control is due to the fact that the enzymes responsible, ultimately for the maintenance of the pool of bioactive GAs, are dependent on 2-oxoglutarate as cofactor. Following, different but complementary experiments were carried out using wild type (WT) and mutant tomato (Solanum lycopersicum L.) plants in the GAs biosynthesis (gib3: moderately deficient, gib2: moderately deficient and gib1: extremely deficient). In the first experiment WT plants and the mutants were used to investigate, in details, the metabolic and physiological impacts of the variation of GA levels in shoot and root tissues. The results showed that, in general, depletion in the endogenous GAs levels promoted greater impacts on leaf tissues when compared to root tissues. In both tissues, gib3 mutant plants were very similar to WT. On the other hand, gib2 and gib1 mutant plants presented drastic and gradual reductions in carbohydrate contents in the foliar tissues, with relatively fewer alterations in roots. Similar behavior was also observed for malate and fumarate. It should be noted that these reductions largely follow the pattern of the reduction of the endogenous GAs content. We also observed that, although the total amino acid pool was not strongly impacted, the individual profile of amino acids was significantly altered with the highest variations occurring in the shoots of gib2 and gib1 mutant plants. These results suggest a differential fine-tuning of metabolism as a function of GA content fluctuations in shoot and roots. The second experiment was conducted with the same genotype as described previously, and the impact of GA reduction on flowering and fruit development was evaluated. Reductions in GA levels affected the reproductive process in gib2 and gib1 mutant plants, thus compromising the natural perpetuation of the genotypes, since floral development was restricted at the bud level. Few variations were observed between WT and gib3 mutant plants in relation to the flowering process, production and final fruit morphology. When evaluating fruit development in three different phases during ripening, we observed that both morphology and metabolism were altered in the early stages, with generally lower values in fruits of gib3. However, at the final stage of the ripening the phenotype is completely recovered. Thus, our results indicate that the changes occurred in the transition from semi autotrophic to completely heterotrophic metabolism and that the reduced GAs content verified in gib3 mutant promotes only a delay in fruit development in good agreement with the action of this hormone being only reported in the early stages of fruit development. The effect of impaired GA biosynthesis appears to be fairly specific, particularly on floral establishment and metabolic reprogramming during fruit development.